2021
DOI: 10.1111/opo.12907
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for myopia and high myopia: A cross‐sectional study among Han and Uyghur students in Xinjiang, China

Abstract: Purpose This study aimed to investigate the prevalence and risk factors for myopia and high myopia among Han and Uyghur students in Xinjiang, China. Methods This cross‐sectional study with a multistage, stratified cluster sampling method was completed in Xinjiang, China. Visual acuity and noncycloplegic refraction were measured. The crude and sex‐ and age‐adjusted prevalence of myopia and high myopia in Han and Uyghur students were compared. Multivariate logistic regression analyses were applied to identify ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Specifically, the prevalence of low myopia was 46.87%, moderate myopia was 8.74%, and high myopia was 2.26%. This prevalence was higher than that of Kazakh students in Urumqi, Xinjiang (11.98%) [8], students in Aksu area (17.91%) [9], Karamay city (39.2%) [10], and other places in Xinjiang (47.70) [11], and Xinjiang in 2014 (39.8%) [12]. However, it was lower than in other areas in China, such as Ningbo City, Zhejiang Province (81.4%) [13] and Tianjin (78.2%) [14].…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, the prevalence of low myopia was 46.87%, moderate myopia was 8.74%, and high myopia was 2.26%. This prevalence was higher than that of Kazakh students in Urumqi, Xinjiang (11.98%) [8], students in Aksu area (17.91%) [9], Karamay city (39.2%) [10], and other places in Xinjiang (47.70) [11], and Xinjiang in 2014 (39.8%) [12]. However, it was lower than in other areas in China, such as Ningbo City, Zhejiang Province (81.4%) [13] and Tianjin (78.2%) [14].…”
Section: Discussionmentioning
confidence: 95%
“…Ueda E 24 and coworkers, based on a cohort study, found that older age and longer axial length were associated with the development of myopic maculopathy. Jing S 25 and coworkers also reported that age was positively associated with high myopia. However, it is not easy to fully explain why age is a risk factor for high myopia.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, consistent with ndings from both domestic and international surveys, the myopia rate among females was higher than that among males. [13][14][15] This trend may be attributed to the relatively lower amount of time females spend engaging in outdoor activities compared to males, and longer periods of close-eye use 16,17 . Research on the prevalence of myopia, both nationally and internationally, is mostly based on cross-sectional studies with a minimum time interval of one year.…”
Section: Discussionmentioning
confidence: 99%